Applications of atomic layer deposition in solar cells. (20th January 2015) - Niu, Wenbin; Li, Xianglin; Karuturi, Siva Krishna; Fam, Derrick Wenhui; Fan, Hongjin; Shrestha, Santosh; Wong, Lydia Helena; Tok, Alfred Iing Yoong
Abstract: Atomic layer deposition (ALD) provides a unique tool for the growth of thin films with excellent conformity and thickness control down to atomic levels. The application of ALD in energy research has received increasing attention in recent years. In this review, the versatility of ALD in solar cells will be discussed. This is specifically focused on the fabrication of nanostructured photoelectrodes, surface passivation, surface sensitization, and band-structure engineering of solar cell materials. Challenges and future directions of ALD in the applications of solar cells are also discussed.